Advances in systemic therapy for non-small cell lung cancer - Miller, Meagan; Hanna, Nasser (BMJ (Online), 2021)
ABSTRACTLung cancer remains a leading cause of cancer related mortality worldwide. Despite numerous advances in treatments over the past decade, non-small cell lung cancer (NSCLC) remains an incurable disease for most patients. The optimal treatment for all patients with locally advanced, but surgically resectable, NSCLC contains at least chemoradiation. Trimodality treatment with surgical resection has been a subject of debate for decades. For patients with unresectable or inoperable locally advanced disease, the incorporation of immunotherapy consolidation after chemoradiation has defined a new standard of care. For decades, the standard of care treatment for advanced stage NSCLC included only cytotoxic chemotherapy. However, with the introduction of targeted therapies and immunotherapy, the landscape of treatment has rapidly evolved. This review discusses the integration of these innovative therapies in the management of patients with newly diagnosed NSCLC.